2018
DOI: 10.3389/fphar.2018.01049
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Pharmacogenetic Studies in Schizophrenia: Efficacy and Agranulocytosis

Abstract: Clozapine is an efficacious atypical antipsychotic for treatment-refractory schizophrenia. Clinical response and appearance of adverse events vary among individual patients receiving clozapine, with genetic and non-genetic factors potentially contributing to individual variabilities. Pharmacogenetic studies investigate associations between genetic variants and drug efficacy and toxicity. To date, most pharmacogenetic studies of clozapine have been conducted through candidate gene approaches. A recent advance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 132 publications
0
16
0
2
Order By: Relevance
“…HLA genetic diversity is also implicated in the modulation of treatment responses in psychiatric conditions, including in the regulation of adverse drug reaction (ADRs) and treatment efficacy. Both candidate gene studies and GWAS have shown that clozapine-induced agranulocytosis is partly mediated by class I and II HLA alleles ( Numataa et al, 2018 ). In a study of treatment response to antipsychotic, we showed that a double amino-acid change in the HLA-A peptide-binding groove was associated with a better response to treatment with Risperidone in patients with schizophrenia (LeClerc et al, 2015).…”
Section: Hla and Treatment Responsesmentioning
confidence: 99%
“…HLA genetic diversity is also implicated in the modulation of treatment responses in psychiatric conditions, including in the regulation of adverse drug reaction (ADRs) and treatment efficacy. Both candidate gene studies and GWAS have shown that clozapine-induced agranulocytosis is partly mediated by class I and II HLA alleles ( Numataa et al, 2018 ). In a study of treatment response to antipsychotic, we showed that a double amino-acid change in the HLA-A peptide-binding groove was associated with a better response to treatment with Risperidone in patients with schizophrenia (LeClerc et al, 2015).…”
Section: Hla and Treatment Responsesmentioning
confidence: 99%
“…Due to the potential for agranulocytosis and a high risk of infection, patients taking clozapine require long-term hematology monitoring. A number of mechanisms for the clozapine-induced agranulocytosis have been explored [25,26]. In macrophages, clozapine affects adhesion, phagocytosis, and reactive oxygen species production [27].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its evident clinical benefit, clozapine use is limited due to clozapine-induced agranulocytosis/granulocytopenia (CIAG). Significant pharmacogenetic studied have explored this phenomenon, as recently reviewed by Numata et al (2018). Several GWAS have been conducted, an initial effort by Goldstein et al, on 161 CIAG cases and 1196 controls of European descent, found genome-wide associations for variants in HLA-DQB1 and in HLA-B (Goldstein et al 2014).…”
Section: Clozapinementioning
confidence: 99%